PENGARUH PROJECT-BASED LEARNING PRODUK KIMIA TERHADAP PEMAHAMAN KONSEP DAN KETERAMPILAN PROSES SAINS SISWA SMA - Anggriani, Frida; Wijayati, Nanik; Susatyo, Eko Budi; Kharomah, Kharomah (Universitas Negeri Semarang, 2019)
Project-based learning is a complex task based on challenging questions or problems, involving students in design, problem solving, decision making, or investigative activities, giving students the opportunity to work autonomously then produce products. The study aims to determine the effect of project-based learning of chemical products on understanding the concepts and science process skills of high school students. The research method was an experiment using modified pretest-posttest group comparison design. The sampling technique used is cluster random sampling. Class XI IPA 5 as an experimental class and class XI IPA 1 as a control class. The analysis technique used is the average difference test, the effect analysis between variables, and the determination of the coefficient of determination. The results obtained by the average learning outcomes and science process skills of the experimental class 80.61 and 80.89 while the control class 77.08 and 74.64. Analysis of influence between variables resulted in biserial coefficient values of 0.33 for learning outcomes and 0.40 for science process skills. Calculation of the coefficient of determination of the effect of project-based learning contributes 10.89% to learning outcomes and 16% to science process skills. Based on the results of the study, it was concluded that project-based learning had an effect on the understanding of concepts and science process skills of class XI students of SMAN 2 Mranggen on solubility and solubility products.